2020
DOI: 10.1128/jvi.01657-19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Altered Virulence of Type O Foot-and-Mouth Disease Virus

Abstract: Under different circumstances, the alteration of several viral genes may give an evolutionary advantage to the virus to maintain its prevalence in nature. In this study, a 70-nucleotide deletion in the small fragment (S fragment) of the viral 5′-untranslated region (5′-UTR) together with one amino acid insertion in the leader protein (Lpro) that naturally occurred in several serotype O foot-and-mouth disease virus (FMDV) strains in China was identified. The properties of two field serotype O FMDV strains, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The cre region is involved in templating uridylation of the RNA primer peptide, VPg (also known as 3B), and the IRES determines the initiation of translation of the viral polyprotein [ 17 , 18 ]. The roles of the S-fragment, the poly-C tract and the PKs in viral replication have not been fully elucidated, however, recent studies have shown that truncations to the S-fragment can affect the ability to control aspects of innate immune response to viral infection [ 19 21 ]. It has also recently been reported that viruses with a deletion within the PK region exhibited an attenuated phenotype in bovine but not in porcine cells, suggesting a role for the PKs in determining viral tropism [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cre region is involved in templating uridylation of the RNA primer peptide, VPg (also known as 3B), and the IRES determines the initiation of translation of the viral polyprotein [ 17 , 18 ]. The roles of the S-fragment, the poly-C tract and the PKs in viral replication have not been fully elucidated, however, recent studies have shown that truncations to the S-fragment can affect the ability to control aspects of innate immune response to viral infection [ 19 21 ]. It has also recently been reported that viruses with a deletion within the PK region exhibited an attenuated phenotype in bovine but not in porcine cells, suggesting a role for the PKs in determining viral tropism [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…STAR+METHODS generated using site-directed mutagenesis. The full-length infectious clone containing the FMDV O/BY/CHA/2010 sequence was generated based on the reverse-genetics system (Yang et al, 2020). All constructed plasmids were analyzed and verified by DNA sequencing.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The construction strategy for the r3B-FMDV and r3B-A/E-FMDV infectious clones was based on the reverse-genetics system that has been developed by our laboratory previously (35). A synonymous substitution led to no changes in amino acids in the 2C was introduced into the viral genome of O/BY/CHA/2010 (mutation of the 691-696 region in 2C from 59-ATTGAC-39→59-ATCGAT-39) to generate a unique ClaI restriction enzyme site.…”
Section: Construction Of the R3b-fmdv And R3b-a/e-fmdv Infectious Clonesmentioning
confidence: 99%
“…All of the constructed plasmids were sequenced. The viral rescue and identification was then performed as described previously (35).…”
Section: Construction Of the R3b-fmdv And R3b-a/e-fmdv Infectious Clonesmentioning
confidence: 99%